Entrepreneurial process in international multiunit franchise outlets: A social capital perspective - Hadjielias, Elias; Dada, Olufunmilola (Lola); Eliades, Kostas (My University, 2021)
This paper examines how social capital facilitates entrepreneurial process in international multiunit franchise outlets, operating under an area development agreement. Despite empirical evidence showing that international multiunit franchisees pursue entrepreneurial objectives, there is shortage of knowledge as to how these occur. This study reveals that micro-level entrepreneurial process in international multiunit franchise outlets (operating under an area development agreement) is bounded within structural, relational and cognitive dynamics. Structural dynamics involve diverse forms of interactions (i.e. horizontal, bottom-up, portfolio, franchisor-franchisee and franchisee peer) and their structural properties (i.e. strong, weak, appropriable, hierarchical and bridging ties), which determine the resources to be mobilized and the activities to be actuated at different phases of the entrepreneurial process. Relational and cognitive dynamics involve interpersonal and collective conditions (i.e. obligations, shared stories, trust and norms), which facilitate or constrain interactions and the entrepreneurial process. The study provides implications for incorporating sociological perspectives in franchisee entrepreneurship research.
Keywords: Entrepreneurial process; Social capital; Franchisee entrepreneurship; International multiunit franchising